SIFAT VENIR DAN KAYU LAPIS 7 JENIS KAYU DARI MALUKU - M I Iskandar; Suwandi Kliwon; Paribotro Sutigno (Pusat Penelitian dan Pengembangan Hasil Hutan, 1987)
The characteristics studied are peeling properties, physical properties of the veneer, gluing properties and some physical and mechanical properties of the plywood (both triplex and multiplex).All logs from the 7 wood species could be peeled satisfactorily in cold condition. Veneer of 0.9 mm and 1.5 mm thickness could be produced at a cutting angle between 91°-93°.Average shrinkage of the veneer is 7%. Average swelling from oven dry condition is 3%.Water resistant, bonding strength for all wood species studied meet Indonesian, Japanese and German standards. Average thickness reduction due to pressing in the plywood manufacturing process is 0.15 mm.Specific gravity of the plywood is about 6 percent higher than that of the wood from which it is made of